High‐intensity focused ultrasound treatment for excessive subcutaneous fat in abdomen, upper arms, and thigh: A pilot study. (9th February 2022) - Lee, Hyun Ji; Lee, Ji Hyun; Bang, Chul Hwan; Jung, Joon‐Yong; Park, Young Min
Abstract: Background: High‐intensity focused ultrasound (HIFU) has been recently introduced as a non‐invasive therapeutic modality for controlling excessive subcutaneous fat. Objective: The efficacy and safety of the HIFU device for sculpting the abdomen, upper arm, and thigh were evaluated. Materials and Methods: Ten subjects with more than 10 mm of subcutaneous fat in the abdomen, upper arm, and/or thigh were recruited. We evaluate mean change in the thickness and circumference of subcutaneous fat of each treated area measured using ultrasound 12 weeks after the procedure, the degree of pain, and subject and practitioner satisfaction 12 weeks after the procedure. Results: The mean change of subcutaneous fat thickness in the abdomen, upper arm, and thigh measured using ultrasound 12 weeks after the procedure was −4.33 ± 2.42, −1.86 ± 1.35, and −1.86 ± 1.35 mm, respectively. Compared with pretreatment, subcutaneous fat thickness of the abdomen and upper arm was significantly reduced ( p  = 0.0020 and p  = 0.0004, respectively), but not in the thigh ( p  = 0.0716). Highest patient satisfaction was for the abdomen. Pain was generally tolerable. Conclusion: The results from the present study indicate HIFU can be an effective and safe therapeutic modality for removing excessive subcutaneous fat in humans.